DEVELOPING MUSIC TALENT IN BASIC EDUCATION - Koga, Fabiana Oliveira [UNESP]; Tolon, Rosa Maria (Unesp-faculdade Ciencias & Letras, 2019)
Music education and the specialized attention to the talented students are provided by the Law 13.278/16 and Law 13.234/15, both stemming from the Law 9394/96. However, many Brazilian students have no access to music education, neither a specialized educational service. If the music subject were implemented in all schools, as happens with physical education and arts, many students could benefit from this teaching, be identified and develop their potentialities. That is why this theoretical essay aims to discuss about music teaching and the development of music talent, so this subject can be increasingly discussed and, perhaps, can mobilize managers of basic and higher education for the relevance of this modality of education for human development and, in the case of musical talent, quality of life and opportunity for those who manifest it.
Keywords: Education; Special Education; Music Education; Music talent